2007
DOI: 10.1158/1055-9965.epi-06-0732
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Physical Activity and Mammographic Breast Density Characteristics

Abstract: Increased mammographic breast density is considered an intermediate marker of breast cancer risk. Physical activity is believed to reduce breast cancer risk; however, its effect on breast density is not well understood. We studied the association between recreational physical activity and mammographic characteristics of the breast among a population of premenopausal and postmenopausal women enrolled as controls (n = 728) in a case-control study of mammographic breast density and breast cancer. Women were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…The average estimated MET hours/week was 15.7 (SD 16.7) among ''healthy'' controls and 13.0 (SD 15.5) among ''benign breast disease'' controls. 18 A cross sectional study was carried out in 620 women participants in the Dutch EPIC using the same questionnaire model and the same PA indexes used in our analyses. Overall, in the Dutch study no association between a combined index of PA at work, recreational and household activities and mammographic percent density was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average estimated MET hours/week was 15.7 (SD 16.7) among ''healthy'' controls and 13.0 (SD 15.5) among ''benign breast disease'' controls. 18 A cross sectional study was carried out in 620 women participants in the Dutch EPIC using the same questionnaire model and the same PA indexes used in our analyses. Overall, in the Dutch study no association between a combined index of PA at work, recreational and household activities and mammographic percent density was found.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested an inverse association between PA and high MBD 12,13 or a positive association with hours of inactivity, 14 while others reported no association. 10,[15][16][17][18] We have carried out a study on 2,001 healthy women to prospectively investigate the influence of baseline individual characteristics related to dietary and life style habits on MBD, as assessed by mammographic examinations (MEs) performed 5 years after the enrolment in the cohort. We have previously reported results on the association between selected dietary habits and high MBD, 19 and in the present study we focused on the role of PA.…”
mentioning
confidence: 99%
“…We used data from controls drawn from the Mammograms and Masses Study (MAMS), a case-control study of estrogen metabolites, mammographic breast density, and breast cancer risk. Details of the study methodologies have been presented elsewhere (26). In brief, 869 cancer-free women and 264 recently diagnosed breast cancer cases were recruited into the MAMS through the Magee-Womens Hospital Mammographic Screening and Diagnostic Imaging Program in the greater Pittsburgh area between September 2001 and May 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, at least two reviews of the epidemiologic literature failed to show significantly altered breast cancer risk in postmenopausal women with higher insulin-like growth factor-1 levels (22,23). Likewise, we excluded mammographic density from our biological model because recent research has generally shown no association between physical activity and breast density (24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%